The Determinants of Health Status: A Cross-Country Analysis (The Pakistan Development Review, 1994)
An analysis of health status is an important aspect of human resource development. Improvements in health do not only improve the productivity of the labour force, but they also help to improve the impact of other forms of human capital formation, e.g. education. In most developing countries health status is difficult to determine as the question arises as to what measures should be used as indicators of health status. At a general level most of the demand or production function considerations are obtained by aggregating over the micro factors. I However, in the case of health status micro and macro measures may not be perfectly correlated; In most cross-country studies life expectancy at birth or the infant mortality rate are taken as indicators of health status. Other measures which can be used to indicate such improvements in health status are age and diseasespecifrc mortality or morbidity and life expectancy. However, the improvement in health status can be observed most obviously from increases in life expectancy which is a better measure for cross country comparison than age and diseasespecific mortality or morbidity, which are more difficult to compare at the international level.